Exchange bias and magnetic memory effect in hole doped Nd0.78Sr0.22CoO3 nanoparticles. Issue 41 (16th September 2022) - Giri, Neepamala; Biswas, Bohnni Shikha; Sengupta, Payal; Ray, Ruma
Abstract : Nd0.78 Sr0.22 CoO3 nanoparticles having 89 nm average particle size are synthesized by standard sol–gel techniques. Abstract : Nd0.78 Sr0.22 CoO3 nanoparticles having 89 nm average particle size are synthesized by standard sol–gel techniques. Structural and morphological characterization is performed by X-ray diffraction and FESEM images. DC magnetization studies in the range 1.6 K to 300 K reveal the disordered magnetic phase below 36 K. Existence of this disordered magnetic phase is substantiated by the magnetic memory effect. A significant upturn in the ZFC magnetization below 4.5 K, which is a signature of a dominant ferromagnetic (FM) component, is observed. This FM component may be attributed to the uncompensated (UC) spins at the surface of Nd0.78 Sr0.22 CoO3 nanoparticles. The presence of the interface of these two magnetic components with significantly different anisotropy results in the exchange bias effect.